Sucrose Malabsorption in Greenland. Issue 5804 (1st April 1972) - McNair, A.; Gudmand-Høyer, E.; Jarnum, S.; Orrild, Lis
Abstract : In a population study on the western coast of Greenland the incidence of sucrose malabsorption was estimated by means of sucrose tolerance tests in 190 persons. Small-intestinal disaccharidase activity was estimated in 19 patients. Sucrose malabsorption was present in 10·5% of the cases studied—a surprisingly high figure and much higher than the incidence reported elsewhere in the world. This incidence is, however, lower than that of lactose malabsorption in Greenland Eskimos (54%). In contrast to lactose malabsorption, sucrose malabsorption is present from birth; this may have important clinical implications since chronic diarrhoea and malnutrition are fairly common during infancy in Greenland.